A CONTRIBUIÇÃO DO DESENVOLVIMENTO DAS COMPETÊNCIAS SOCIOEMOCIONAIS NA CONSTRUÇÃO DO PROJETO DE VIDA NA EDUCAÇÃO PROFISSIONAL E TECNOLÓGICA (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2022)
To face the challenges of the 21st century, there is a need for professionals who master new technologies and who have socioemotional skills. This work, with a qualitative approach, analyzes the perception of the contribution of the development of socioemotional skills in the construction of the life project in Professional Technological Education. For data collection a questionnaire was applied via Google Forms to 34 students and semi-structured interviews were conducted with 2 professors and an human resources manager from a multinational. Through the results obtained, it was observed that around 75% of students have an established short, medium and long term life project; Among the essential competences for the future, only 29.4% of students chose the competence “autonomy” and only 64.7% “self-knowledge and self-care”, however, the 3 interviewees emphasized these three competences mentioned as fundamental for the individual. can build a successful life project.
Keywords: Socioemotional Skills. Life Project. Professional and Technological Education.